Experimental Study of Feed Rate Related Factors of Combine Harvester Based on Grey Correlation. Issue 17 (2018) - Zhang, Yawei; Chen, Du; Yin, Yanxin; Wang, Xin; Wang, Shumao
Abstract: In the process of harvesting, the feed rate of combine harvester could be affected by many factors, such as crop parameters, operation status parameters and working condition. The objective of this paper is to ensure the relationship of feed rate and its related factors, and the impact intensity of each factor on feed rate. Based on the grey relative analysis method, the correlation analysis of feed rate related parameters was made and the correlation degree of each related parameter on the feed rate was obtained in this paper. The feed rate related factors (e.g. operation speed, crop density and the torque and rotating speed of feeding auger, inclined conveyor and threshing cylinder et. al) was obtained from the multi-information collection system for grain combine harvester. Then, the correlation degree of feed rate related factors was calculated based on grey correlation by assign to correlation weight and time delay compensation. Experimental study result showed that the correlation degrees of operation speed and the torque of threshing cylinder with the feed rate of combine harvester are the highest. The correlation coefficient of operation speed and the torque of threshing cylinder on feed rate were respectively 0.8396 and 0.7915. Compared to other factors, the changes of operation speed and the torque of threshing cylinder could better reflect the tendency of the feed rate. This paper provides a theoretical support for feed rate detection and the fundamental basis for operational control of combine harvester.